2011
DOI: 10.1177/0192513x11406228
|View full text |Cite
|
Sign up to set email alerts
|

Will Marriage Matter? Effects of Marriage Anticipated by Same-Sex Couples

Abstract: The current study used an online survey to explore the anticipated impact of legalized marriage on partners in same-sex couples living in California. These data were gathered prior to the California Supreme Court decision in May 2008 legalizing same-sex marriage, which held sway for 5 months before California Proposition 8 eliminating same-sex marriage was passed by a voter referendum. In addition to administering three quantitative measures (Gay and Lesbian Acceptance & Social Support Index, Anticipated Impac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 32 publications
0
34
0
2
Order By: Relevance
“…The CSI was developed using item response theory, and demonstrates greater power to detect relationship satisfaction than other widely used measures (Funk & Rogge, 2007). It has demonstrated acceptable reliability with same-sex couples (Shulman, Gotta, & Green, 2012). It has demonstrated acceptable reliability with same-sex couples (Shulman, Gotta, & Green, 2012).…”
Section: Couple Relationship Satisfactionmentioning
confidence: 99%
“…The CSI was developed using item response theory, and demonstrates greater power to detect relationship satisfaction than other widely used measures (Funk & Rogge, 2007). It has demonstrated acceptable reliability with same-sex couples (Shulman, Gotta, & Green, 2012). It has demonstrated acceptable reliability with same-sex couples (Shulman, Gotta, & Green, 2012).…”
Section: Couple Relationship Satisfactionmentioning
confidence: 99%
“…This is somewhat similar to findings by Riggle, Rostosky, and Horne (2009), which found that among GLBT individuals living in states preparing to vote on SSM bans, those individuals experienced more discrimination and decreased mental health. At the same time, research demonstrates that perceiving access to SSM is related to feelings of life security and protection from social discrimination as well as stronger couple relationships (Shulman, Gotta, & Green, 2012).…”
Section: Impact Of Queering Marriage Through a Family Lensmentioning
confidence: 99%
“…Social security assistance programs often base their benefits and eligibility on marital status and those who are legally married have access to, "their own and their living and deceased partner's benefits" (Kubasek, Glass, and Cook, 2011, p. 968). Even for those same-sex couples that were legally allowed to marry in their state, they are not covered under the federal benefits that heterosexual couples would normally be covered under (Shulman, Gotta, and Green, 2012).…”
Section: Same-sex Marriagementioning
confidence: 99%
“…Kubasek, Glass, and Cook (2011) and Riggle, Rostosky, and Prather (2006) argue that a lack of change in policies could lead to stress due to vulnerabilities which can then effect relationship quality between parents. Shulman, Gotta, and Green (2012) argue that a change in policies would provide same-sex couples and their families a sense of security knowing that they are protected under the law. Even with the legalization of same-sex marriage, some same-sex families still face institutional discrimination.…”
Section: Same-sex Marriagementioning
confidence: 99%